A Multidisciplinary Survey to Assess Facilitators and Barriers to Successful Organ Donation in the Intensive Care Unit. (June 2019) - Oczkowski, Simon J. W.; Durepos, Pamela; Centofanti, John; Arsenau, Erika; Dhanani, Sonny; Cook, Deborah J.; Meade, Maureen O.
Introduction: Rates of successful organ donation vary between otherwise comparable intensive care units (ICUs). The ICU staff have a unique perspective into the facilitators and barriers underlying this variation in successful deceased organ donation. Research Question: What do ICU staff perceive to be the most meaningful facilitators and barriers to deceased organ donation? Design: We designed and conducted a survey of all disciplines working in the ICU to ascertain the perceived facilitators and barriers to donation in an academic tertiary care hospital. Survey reliability was assessed using Cronbach α. Factor analysis was used to assess construct validity and identify potentially redundant survey items. Results: We had responses from 108 ICU staff, including nurses (n = 75), respiratory therapists (n = 14), physicians (n = 12), chaplains (n = 2), as well as social work, pharmacy, physiotherapy, and occupational therapy (n = 1 each). Perceived facilitators included availability of organ donation organization coordinators, explicit institutional support for donation, ICU staff culture toward donation, standardized order sets for donation, presence of ICU staff with donation experience, and bedside nurse presence at discussions about donation. Perceived barriers included ICU staff ruling out potentially suitable donors before consulting a donor coordinator, physician communication skills, low priority for organ donation among operating room staff, limited family understanding of patient prognosis and organ donation, and limited emotional readiness of families to discuss donation. Discussion: Several staff-perceived facilitators and barriers to deceased organ donation were identified in the ICU. Future research could identify strategies to promote these facilitators and overcome barriers.